Volʹga Ìvanova, Asabìstyâ arhìvy Belarusì kanca XVIII–nač. XXI st., Mìnsk 2014, ss. 403. - Syta, Krzysztof (Archiwa – Kancelarie – Zbiory, 2018)
Volʹga Ìvanova, Asabìstyâ arhìvy Belarusì kanca XVIII–nač. XXI st., Mìnsk 2014, ss. 403.